Strategi Pengembangan dan Pemasaran Produk Menggunakan Sentra Wisata Kuliner UMKM Minuman di Kelurahan Keputih Kecamatan Sukolilo Kota Surabaya - Asnanda Fairuz Tsuraya; Yanda Bara Kusuma (STIPAS Tahasak Danum Pambelum Keuskupan Palangkaraya, 2023)
For approximately 3 months, these programs can be carried out well and can be accepted by the residents of Keputih Village even though there are several obstacles or obstacles that become a challenge for students to find solutions to these problems so that the planned programs can run more optimally and are expected to help develop MSMEs and business potential in Keputih Village, Sukolilo District, Surabaya City well. The Thematic Real Work Lecture of Merdeka Belajar Kampus Merdeka (KKNT MBKM) has a work program that has been implemented by the University of National Development